2010
DOI: 10.3382/ps.2009-00281
|View full text |Cite
|
Sign up to set email alerts
|

Transport stress in broilers. II. Superoxide production, adenosine phosphate concentrations, and mRNA levels of avian uncoupling protein, avian adenine nucleotide translocator, and avian peroxisome proliferator-activated receptor-γ coactivator-1α in skeletal muscles

Abstract: The effect of transport stress on superoxide production and adenosine phosphate concentration in addition to avian uncoupling protein (avUCP), avian adenine nucleotide translocator, and avian peroxisome proliferator-activated receptor-gamma coactivator-1alpha mRNA levels of skeletal muscles in broilers was investigated. Arbor Acres chicks (n = 360, 46 d old, males) were randomly allotted to 1 of 5 treatments: unstressed control, 45-min (short-term) transport with 45-min (short-term) recovery, 45-min transport … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 50 publications
0
28
0
2
Order By: Relevance
“…Many stress factors will lead to an excessive accumulation in ROS production, which may cause oxidative stress, protein and lipid peroxidation and cellular damage, and ultimately affect meat quality. However, ROS can be converted to hydrogen peroxide by SOD, and then hydrogen peroxide is reduced to water and oxygen by CAT and GSH‐PX . Therefore, decreased ROS content and/or improved antioxidant enzyme activity may be beneficial to meat quality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many stress factors will lead to an excessive accumulation in ROS production, which may cause oxidative stress, protein and lipid peroxidation and cellular damage, and ultimately affect meat quality. However, ROS can be converted to hydrogen peroxide by SOD, and then hydrogen peroxide is reduced to water and oxygen by CAT and GSH‐PX . Therefore, decreased ROS content and/or improved antioxidant enzyme activity may be beneficial to meat quality.…”
Section: Discussionmentioning
confidence: 99%
“…Reactive oxygen species (ROS) is produced as an inevitable by-product of normal animal metabolism. Many stress factors will lead to an excessive accumulation in ROS production, which may cause oxidative stress, protein and lipid peroxidation and cellular damage, 26,27 and ultimately affect meat quality. However, ROS can be converted to hydrogen peroxide by SOD, and then hydrogen peroxide is reduced to water and oxygen by CAT and GSH-PX.…”
Section: Discussionmentioning
confidence: 99%
“…ATP concentrations within red and white skeletal muscle fibers from vertebrates (see Refs. 6,11,27,36,56,72,119,146,157,160,164,177,182,200,202,207,219,243,256,265,269,293,294,308). For mammals, red vs. white [CP], P = 0.0006 (two-tailed t test); for all vertebrates combined, red versus white [CP], P = 0.0085 (two-tailed t test).…”
Section: Sources Of Energy That Power Metabolismmentioning
confidence: 99%
“…Zhang et al (2009) reported that transportation of broilers caused an increase in glycogenolysis resulting in glycogen decrease in both breast and thigh muscles. In addition, transport stress was associated with an enhanced skeletal muscle energy metabolism, to mitochondrial superoxide production, acceleration of lipid peroxidation and to induction of cellular damages (Zhang et al 2010). …”
Section: Introductionmentioning
confidence: 99%